A cross sectional study on the crystallization of amorphous Ge2Sb2Te5 films induced by a single-pulse ultraviolet laser. (July 2016) - Zhu, Z.; Liu, F.R.; Yang, J.F.; Fan, Z.K.; Liu, F.; Sun, N.X.
Abstract: In this paper, the crystallization along the film thickness of amorphous Ge2 Sb2 Te5 (a-GST) films induced by a single-pulse ultraviolet laser was investigated by using transmission electron microscopy (TEM) integrated with SAED. TEM observations showed that the crystalline GST (c-GST) was composed of columnar grains at the top surface and equaixed grains inside the film. Moreover, the columnar grains became larger with the increase of laser fluence. A three-dimensional finite element method simulation was further used to elucidate the temperature field by a nanosecond excimer laser in the cross section of the a-GST film. A big temperature gradient obtained at the top surface in the cooling process caused the formation of columnar grains, while columnar grains were gradually substituted by small equaixed grains with the decrease of temperature gradient downwards the film interior. Highlights: Cross sectional study on the crystallization of a-GST film was carried out by TEM observations. Microstructure characteristics in the cross section of a-GST films by a short laser pulse were elucidated. Temperature field through the film thickness was predicted based on a 3D FEM model. The role of temperature gradient for the crystallization of a-GST was discussed.